Training/detraining-induced gender specific functional adaptations of isolated rat heart - Dragojlović Ružičić, Radica; Radovanović, Dragan; Milanović, Zvezdan; Petković, Anica; Jeremić, Jovana; Nikolić Тurnić Tamara; Milosavljević, Isidora; Srejović, Ivan; Živković, Vladimir; Krivokuća, Živko; Jakovljević, Vladimir; Djordjević, Dušica (Vojnosanitetski pregled, 2021)
Background/Aim. Mechanisms responsible for the beneficial effects of aerobic exercise training on cardiovascular function are well known, but detraining effects on myocardial parameters have not been adequately elucidated. Therefore, the study aimed to determine the occurrence and speed of cardiac adaptation reversibility after the cessation of aerobic exercise and to reveal gender differences in achieved effects of training/detraining. Methods. Female and male Wistar albino rats were divided into the following groups: control, trained, and two detrained groups. Hearts were perfused according to the Langendorff technique and the following cardiodynamic parameters were determined: the maximum and minimum rate of pressure development in the left ventricle (dp/dt max and dp/dt min, respectively), systolic and diastolic left ventricular pressure (SLVP and DLVP, respectively), heart rate (HR), and coronary flow. Results. Training significantly reduced values of dp/dt max, dp/dt min, and SLVP in males and females, and coronary flow in males. Detraining caused a reversion of those changes, which was gender-specific. In females, levels of SLVP were higher after 4 weeks of detraining compred to training, and after 2 weeks of detraining. Values of SLVP were lower in both detraining periods compared to training in males. Males had higher coronary flow after 2 weeks of detraining. Simultaneously, coronary flow was reduced in the 4th week of detraining in females. Conclusion. By using a model of the isolated rat heart, the present study confirmed the existence of training-induced changes in cardiac function. Cessation of training was followed by the loss of those adaptations, faster in males than females.